Remote Controlled Weapon Stations – Development of Thought and Technology - Jan F. DOLASIŃSKI (Zdalnie Sterowane Moduły Uzbrojenia – rozwój myśli i techniki, 2020)
The publication presents the Remote Controlled Weapon Station (RCWS) family, designed, produced and developed at Zakłady Mechaniczne (Mechanical Plant) ‘Tarnów’ S.A. in Tarnów (Poland). The paper describes the functionality, scope and purpose of research and development and the prospective directions of its future development. The publication describes the most important functional elements of RCWS, the most important performance parameters as well as scientific and typically engineering issues encountered during the development of this range of products. Additionally, we have provided examples of the use of RCWS family products in military equipment used by the Polish Armed Forces and proposals for use in equipment that is pending implementation. The publication presents the RCWS family, from the least to the most advanced and versatile module. It also touches upon the classification of remote controlled military equipment, as well as the methods of its use on the contemporary battlefield. The publication also illustrates the benefits of using remote controlled equipment on the battlefield – such as providing complete, or at least sufficient isolation of the soldier from the dangers of the battlefield, while supporting correct decision-making and enabling advanced observation, recon and tracking of selected targets.
Keywords: Zdalnie Sterowane Moduły Uzbrojenia